Prevalence and genetic diversity of multidrug-resistant Salmonella Typhimurium monophasic variant in a swine farm from China - Zhou, Lin; Zhang, Tie-Jun; Zhang, Weicheng; Xie, Chengjiang; Yang, Ye; Chen, Xuan; Wang, Qin; Wang, Hong-Ning; Lei, Chang-Wei (Frontiers in Microbiology, 2023)
Salmonella 4,[5],12:i:-, a monophasic variant of S. Typhimurium, has become a global serovar causing animal and human infections since its first emergence in the late 1980s. Several previous studies showed the increasing prevalence of S. 4,[5],12:i:- in China, most of which were from swines with multidrug resistance (MDR) profiles. However, the molecular characteristic and evolution of S. 4,[5],12:i:- in the same swine farm is still unknown. In this study a total of 54 S. enterica strains were isolated from different fattening pigs aged 1, 3, and 6 months, most of which belonged to S. 4,[5],12:i:-. Whole genome sequencing revealed that all 45 S. 4,[5],12:i:- strains belonged to ST34, and further divided into two different ribosomal STs and nine different core genome STs. Phylogenetic analysis of 286 S. 4,[5],12:i:- strains in China, including 241 from EnteroBase Salmonella database, revealed the genetic diversity of S. 4,[5],12:i:- and indicated that S. 4,[5],12:i:- in this swine farm might have multiple origin. Three different IncHI2 plasmids carrying various resistance genes were characterized by Nanopore sequencing, and could be conjugated to Escherichia coli. The colistin resistance gene mcr-1 and ESBLs gene blaCTX-M-14 were co-located on the chromosome of one strain. The dynamic changes in antimicrobial resistance regions and transferability of IncHI2 plasmids, as well as the chromosomal location of resistance genes, facilitated the diversity of the antimicrobial resistance characteristics in S. 4,[5],12:i:-. Since the swine farm is regarded as the important reservoir of MDR S. 4,[5],12:i:-, the prevalence and evolution of S. 4,[5],12:i:- from swine farms to pig products and humans should be continually monitored.